Complexity and selection: considerations about the implications for organizational change (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
Some considerations concerning the article entitled “Complexity and Selection: implications for organizational change”, by Sigrid Glenn and Maria Mallot are discussed. It is important to draw the organizational boundaries as well as to describe and classify the complex contingencies involved in an organization. The need for a selectionist approach is highlighted by the utility of the concept of metacontingencies. Moreover, the role of advertisement in the organization survival is discussed.